UPAYA PROMOTIF PREVENTIF DAN PENGENDALIAN HIPERTENSI OLEH PUSKESMAS TEGALREJO KOTA SALATIGA - KUBA, SANLY RAMBU; NUSAWAKAN, ARWYN WEYNAND; PUTRA, KUKUH PAMBUKA (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Hypertension causes death in the population of 17.9 billion per year. Hypertension in 2013 was 28.5% and continued to increase to 34.1% in 2018 in Indonesia. The research used descriptive qualitative method. This study also uses a descriptive quantitative design as a justification for the people who live in the Tegalrejo Health Center area. The purpose of this study was to describe the promotion, prevention and control of hypertension by the Tegalrejo Health Center, Salatiga City. Determination of the sample using purposive sampling to health workers who are responsible for the promotion and prevention of hypertension at the Tegalrejo Health Center and simple random sampling technique to the people who live in the fostered area of the Tegalrejo Health Center. Qualitative data analysis using Miles and Huberman technique then quantitative data is analyzed using quantitative description. The results of this study found that promotive, preventive and controlling hypertension efforts have been implemented starting from the existence of counseling to the community related to hypertension, early detection, partnerships and also community empowerment. Quantitative data as a justification shows that 64% of the public are not aware of the existence of a hypertension prevention program by the health center, as many as 76% of the community also cannot understand the hypertension prevention program, and there are 67% of the community who do not participate in counseling, then about 65% of the people who do not receive brochures and leaflet related to hypertension. Based on the data on the behavior of people living in the Puskesmas area, it is quite good, where about 66% of the people routinely check their health, 52% do not smoke, 66% are diligent in doing physical activities, and as many as 81% are on a salt diet, 69% get adequate rest, %), and as many as 87% of the people manage stress. Conclusion: Tegalrejo Health Center has made efforts to promote, prevent and control hypertension including counseling, early detection, partnership, and community empowerment. This research can still be continued using a quantitative design by combining variables.